Breast Cancer Series: Hormone Therapy - Karen C. Daily; Martha C. Monroe (EDIS)
Women who are at high risk of getting breast cancer and women who have had breast cancer may be prescribed daily oral medications to block the estrogen receptor site or decrease the production of estrogen. This 2-page fact sheet describes various hormone therapy options. It is part of a 12-part Breast Cancer series. Written by Karen C. Daily and Martha C. Monroe and published by the UF Department of Family Youth and Community Sciences, June 2011.